1994
DOI: 10.1111/j.1365-2605.1994.tb01202.x
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous measurement of sperm LDH, LDH‐X, CPK activities and ATP content in normospermic and oligozoospermic men

Abstract: Total lactate dehydrogenase (LDH), LDH-X, creatine phosphokinase (CPK) activities and ATP content were measured in washed spermatozoa from 188 normospermic and 94 oligozoospermic men. These four biochemical parameters were significantly higher (p < 0.001) in spermatozoa from oligozoospermic men than in those from normospermic men and were related inversely to sperm concentration. In oligozoospermic men the activity of sperm LDH and LDH-X was related significantly to sperm CPK activity (r = 0.5486 and r = 0.444… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 18 publications
2
14
0
Order By: Relevance
“…These data indicate that in normozoospermic men, the global DNA methylation profile is not affected significantly by structural and functional differences between sperm subpopulations. The extensive conservation of the DNA methylation status is especially surprising if we consider that differences have been described also at the metabolic level of “poor” quality spermatozoa which could theoretically influence the DNA methylation process [7], [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data indicate that in normozoospermic men, the global DNA methylation profile is not affected significantly by structural and functional differences between sperm subpopulations. The extensive conservation of the DNA methylation status is especially surprising if we consider that differences have been described also at the metabolic level of “poor” quality spermatozoa which could theoretically influence the DNA methylation process [7], [8].…”
Section: Discussionmentioning
confidence: 99%
“…The rationale behind selection is mainly related to a predicted higher functional competency and a higher genomic integrity of selected spermatozoa. Interestingly enough, despite the same testicular environment, biochemical markers [7], [8] as well as DNA integrity [9][12] show differences in distinct sperm fractions belonging to the same individual. It is still unknown whether these fractions also show differences in their methylation level.…”
Section: Introductionmentioning
confidence: 97%
“…Orlando et al evaluated total LDH and LDH-C 4 activity in normospermic and oligospermic males and reported that the activity of total LDH was 2.2 times higher in oligospermic males than in normospermic males. They also reported a negative correlation between LDH activity and sperm concentration (35). Noguera et al found that LDH-C 4 activity level differs significantly between fertile and infertile males (36).…”
Section: Discussionmentioning
confidence: 99%
“…lactate dehydrogenase-C4 isoenzyme (Casano et al, 1991;Orlando et al, 1994) and NADH-diaphorase (Gavella & Lipovac, 1992, Gavella et al, 1995, and (ii) to investigate the physiological relevance of SODlike activity in human spermatozoa, by examining its relationship with experimentally-induced lipid peroxidation. lactate dehydrogenase-C4 isoenzyme (Casano et al, 1991;Orlando et al, 1994) and NADH-diaphorase (Gavella & Lipovac, 1992, Gavella et al, 1995, and (ii) to investigate the physiological relevance of SODlike activity in human spermatozoa, by examining its relationship with experimentally-induced lipid peroxidation.…”
Section: Introductionmentioning
confidence: 99%